Crowding out effects of government spending - Barry, Frank; Devereux, Michael B. (Economic & Social Studies, 1992)
This paper surveys the recent theoretical literature on the linkage between government spending and the real economy. Two broad frameworks are explored. Nee-Keynesian models deal with economies characterised by wage or price rigidities, and unemployment. Neo-classical models assume a frictionless economy with perfect wage and price flexibility. In contrast to traditional textbook analysis of fiscal policy however, both models stress the intertemporal dimension of policy, and the rOle of private sector expectations concerning the future path of policy. The two frameworks are used to analyse the response of macroeconomic aggregates to cuts in government spending that may be either temporary or permanent. In most, but not all cases, the results suggest that cuts in government spending will be associated with at least temporary reductions in output.
Keywords: government spending; Fiscal policy; Macroeconomics